Chemomechanical Motion of a Self‐Oscillating Gel in a Protic Ionic Liquid. (20th November 2018) - Masuda, Tsukuru; Ueki, Takeshi; Tamate, Ryota; Matsukawa, Ko; Yoshida, Ryo
Abstract: An autonomous swelling–deswelling oscillation of polymer gels in a hydrated protic ionic liquid (PIL) as a proton source for the Belousov–Zhabotinsky (BZ) reaction is presented. Methylammonium hydrogen sulfate ([maH + ][HSO4 − ]) was employed as the PIL because it provides stable redox oscillation in the BZ reaction. Due to the significantly higher p K a for [maH + ][HSO4 − ] than those for conventional proton sources for the BZ reaction, chemomechanical oscillation can be expected under weaker acidic conditions. The self‐oscillating polymer was designed as a ternary random copolymer of N ‐isopropylacrylamide, N ‐(3‐aminopropyl)methacrylamide, and the Ru(bpy)3 moiety as a catalyst for the BZ reaction. The copolymer exhibited spontaneous soluble–insoluble oscillation in hydrated [maH + ][HSO4 − ] containing NaBrO3 and malonic acid. Macroscopic swelling–deswelling oscillation of the porous bulk gel prepared by covalently connecting microgel particles was also observed. Abstract : Eine autonome An‐/Abschwell‐Oszillation von Polymergelen wurde in einer wässrigen protischen ionischen Flüssigkeit (PIL) als Protonenquelle für die Belousov‐Zhabotinsky(BZ)‐Reaktion erreicht. Die PIL fungiert als Medium für die BZ‐Reaktion und ist ein vielversprechendes Material für die Entwicklung selbstoszillierender Gele unter milderen Bedingungen.